Adsorbing vs. Nonadsorbing Tracers for Assessing Pesticide Transport in Arable Soils. Issue 1 (14th September 2017) - Torrentó, Clara; Prasuhn, Volker; Spiess, Ernst; Ponsin, Violaine; Melsbach, Aileen; Lihl, Christina; Glauser, Gaétan; Hofstetter, Thomas B.; Elsner, Martin; Hunkeler, Daniel
Abstract : Core Ideas: Atrazine preferential flow shortly after application was governed by soil type. Injection of atrazine at depth enhanced preferential flow. Uranine realistically illustrated the rapid and significant atrazine breakthrough. In reserve, bromide mimicked early atrazine breakthrough only with moraine soil. Using dye tracers as pesticide surrogates might assist in making sustainable decisions. The suitability of two different tracers to mimic the behavior of pesticides in agricultural soils and to evidence the potential for preferential flow was evaluated in outdoor lysimeter experiments. The herbicide atrazine [6‐chloro‐ N ‐ethyl‐ N ′‐(1‐methylethyl)‐1, 3, 5‐triazine‐2, 4‐diamine] was used as a model compound. Two tracers were used: a nonadsorbing tracer (bromide) and a weakly adsorbing dye tracer (uranine). Two soils that are expected to show a different extent of macropore preferential flow were used: a well‐drained sandy‐loamy Cambisol (gravel soil) and a poorly drained loamy Cambisol (moraine soil). Conditions for preferential flow were promoted by applying heavy simulated rainfall shortly after pesticide application. In some of the experiments, preferential flow was also artificially simulated by injecting the solutes through a narrow tube below the root zone. With depth injection, preferential leaching of atrazine occurred shortly after application in both soil types, whereas with surface application, it occurred only in the moraine soil. Thereafter, atrazine transport was mainly through the porous soil matrix, although contributions of preferential flow were also observed. For all the application approaches and soil types, after 900 d, <3% of the applied amount of atrazine was recovered in the drainage water. Only uranine realistically illustrated the early atrazine breakthrough by transport through preferential flow. Uranine broke through during the first intense irrigation at the same time as atrazine. Bromide, however, appeared earlier than atrazine in some cases. The use of dye tracers as pesticide surrogates might assist in making sustainable decisions with respect to pesticide application timing relative to rainfall or soil potential for preferential flow.